Identifikasi Spesies Cabai Rawit (Capsicum spp.) Berdasarkan Daya Silang dan Karakter Morfologi - Undang, U; Syukur, Muhamad; ,, Sobir (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2015)
ABSTRACTThe chili consists of several species, five of which have been cultivated, namely C. annuum, C. chinense, C. frutescens, C. baccatum, and C. pubescens. The classifications of these species are based on: 1) morphological characters, especially floral morphology, 2) crossability between species, and 3) fertile hybrids between species. Species C. baccatum and C. pubescens can be easily identified and distinguished from one another, because there are obvious differences in the two species. However the species C. annuum, C. chinense, and C. frutescens has many common characteristics, so it is difficult to distinguish morphologically. The purpose of this study was to identify capsicum species based on crossability and morphological characters. The crossability experiment was done in housing area TDP 2 Ciampea Bogor from January to December 2013 and the morphological characteristics at Leuwikopo experimental station, IPB. The morphological characters experiment was arranged in randomized complete block design (RCBD) with three replications. Data were collected on successful crosses, seed viability of successful crosses and morphological characters based on descriptor for capsicum IPGRI. The percentage of successful crosses involving IPBC10 and IPBC145 (C. annuum) as female parents and 20 genotypes as male parents ranged between 0-90%; and using IPBC295 (C. frutescens) as female parent was 40%. Genotypes which had successful results equals 40% were alleged as C. frutescens species (IPBC61, IPBC139, IPBC63, IPBC163, IPBC289, IPBC288, IPBC294 and IPBC285). Principal component and of clusters analysis suggests that there are two species groups, i.e. C. annuum and C. frutescens.Keywords: capsicum, cluster analysis, crossing, genotypes, principal component analysis